If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -7) = 25 Reorder the terms: -1(-7 + x) = 25 (-7 * -1 + x * -1) = 25 (7 + -1x) = 25 Solving 7 + -1x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 25 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 25 + -7 -1x = 25 + -7 Combine like terms: 25 + -7 = 18 -1x = 18 Divide each side by '-1'. x = -18 Simplifying x = -18
| x^3+0.5x^2+x+8=0 | | 1/2(2x^3)^3 | | 14x+y=58 | | .03x-.1=2.6 | | 2S+T=-1 | | 95/(19/6) | | 3/9x3/4 | | e^3=2.718 | | 0.625x^2+8x=300 | | Y=5/6*6-3 | | 3w+4=-14 | | x/5-3=11 | | (1/2)3.14(.25) | | -7.8(x+6.5)=-25.74 | | Y=5/6*12-3 | | 5n=-1n+1 | | -2(x-5)=-20 | | 3u^2-108u=0 | | f(x)=-3t+4 | | -1/5(x-4)=-2 | | 1/2×w=3/8 | | 7.35b=29.4 | | .6X=640 | | -2(t-1)+8=30 | | x+32+90=180 | | 8/3w=-1 | | 4(1+5n)=10(2n-7) | | 21=42-3r | | w-4-12=3 | | 5x-12-3x=8 | | 36+6(8x+3)=36x-12 | | -2*4-9/3 |